Advancement Of Educational Games To Help Primary School Students' Capacity: Kemajuan Permainan Edukasi Untuk Membantu Kapasitas Penangkapan Siswa Sekolah Dasar - Septi Eirlangga, Yofhanda; Ulya Mega Wahyuni; Silky Selfira (KPN Kopertis X, 2024)
The development of information technology from time to time continues to develop and increase, including in the field of education. The use of information technology in elementary school education is very necessary for various purposes, including learning media. Apart from being used as a learning medium, information technology can also be used to develop knowledge. As time goes by, technology currently has a big influence on the teaching and learning process, from elementary school to higher levels. In the increasingly rapid development of technology that is interesting for children and adults to enjoy, there are even some elementary schools that provide some technology in the teaching process. By using technology as an innovation by teachers, it can be believed that the teaching and learning process will be more interesting and can improve student learning outcomes. If technology is used or utilized in the learning process, the teaching and learning process can be maximized. Information technology has a very important role, especially in the world of education.